An exploratory review of investments by development actors in health workforce programmes and job creation - Remco van de Pas; Linda Mans; Myria Koutsoumpa (BMC, 2023)
Abstract The World Health Organization's Global Strategy on Human Resources for Health: Workforce 2030 identified a projected shortfall of 18 million health workers by 2030, primarily in low- and middle-income countries. The need for investment was re-enforced by the 2016 report and recommendations of the United Nations High-Level Commission on Health Employment and Economic Growth. This exploratory policy tracing study has as objective to map and analyse investments by bilateral, multilateral and other development actors in human resources for health actions, programmes and health jobs more broadly since 2016. This analysis will contribute to the accountability of global human resources for health actions and its commitment by the international community. It provides insights in gaps, priorities and future policies' needs. The study follows an exploratory rapid review methodology, mapping and analysing the actions of four categories of development actors in implementing the ten recommendations of the United Nations High-Level Commission on Health Employment and Economic Growth. These four categories of actors include (A) bilateral agencies, (B) multilateral initiatives, (C) international financial institutions and (D) non-state actors. Analysing the data generated via this review, three trends can be observed. Firstly, while a broad range of human resources for health actions and outputs have been identified, data on programme outcomes and especially on their impacts are limited. Secondly, many of the programmatic human resources for health actions, often funded via bilateral or philanthropic grants and implemented by non-governmental organisations, seemed to be rather short-term in nature, focusing on in-service training, health security, technical and service delivery needs. Despite the strategic guidance and norms developed by multilateral initiatives, such as the International Labour Organization-Organisation for Economic Co-operation and Development-World Health Organization Working for Health programme, has it been for several development projects difficult to assess how their activities actually contributed to national human resources for health strategic development and health system reforms. Lastly, governance, monitoring and accountability between development actors and across the policy recommendations from the United Nations High-Level Commission on Health Employment and Economic Growth could be improved. There has been limited actionable progress made for the enablers required to transform the workforce, including in the domain of generating fiscal space for health that would strengthen jobs in the health sector, the development of health workforce partnerships and its global agenda, and the governance of international health workforce migration. In conclusion, one can observe that global health workforce needs are much recognised, especially given the impact of the Covid-19 pandemic. However, 20 years after the Joint Learning Initiative on Human Resources for Health, there is still an urgent need to take shared responsibility for international cooperative action for overcoming and addressing persistent underinvestment in the health workforce. Specific policy recommendations are provided to this end.